2017
DOI: 10.3384/ecp17144402
|View full text |Cite
|
Sign up to set email alerts
|

Towards Finding the Optimal Bucket Filling Strategy through Simulation

Abstract: The purpose of earth-moving equipment like wheel loaders is to engage with the ground or other material. It is therefore obvious that the bucket filling phase must be included when studying optimal machine control over a complete working cycle because total productivity and efficiency of the machine are to a large extent determined by it. This paper reports and discusses the results of research into how to utilize Discrete Element Method simulations in combination with Optimal Control to find the optimal bucke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…An overview of the research from the late 1980s to 2009 can be found in [3]. Previous research has focused on computer vision in order to characterize piles [4][5][6], the motion planning of bucket-filling trajectories [4,[7][8][9], and loading control. The control strategies can be divided into trajectory control [8,10] and force-feedback control [11,12].…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the research from the late 1980s to 2009 can be found in [3]. Previous research has focused on computer vision in order to characterize piles [4][5][6], the motion planning of bucket-filling trajectories [4,[7][8][9], and loading control. The control strategies can be divided into trajectory control [8,10] and force-feedback control [11,12].…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…Previous research has focused on computer vision in order to characterize piles [4][5][6], the motion planning of bucket-filling trajectories [4,[7][8][9], and loading control. The control strategies can be divided into trajectory control [8,10] and force-feedback control [11,12]. The former aims to move the bucket along a pre-defined path, which is limited to homogeneous media, such as dry sand and gravel.…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…An overview of the research from the late 1980's to 2009 is found in [3]. Previous research has focused on computer vision for characterizing the pile [4,5,6], motion planning of bucket filling trajectories [7,4,8,9], and of loading control. The control strategies can be divided in trajectory control [10,8] or force-feedback control [11,12].…”
Section: Related Workmentioning
confidence: 99%
“…Previous research has focused on computer vision for characterizing the pile [4,5,6], motion planning of bucket filling trajectories [7,4,8,9], and of loading control. The control strategies can be divided in trajectory control [10,8] or force-feedback control [11,12]. The former aims to move the bucket along a pre-defined path, which is limited to homogeneous media such as dry sand and gravel.…”
Section: Related Workmentioning
confidence: 99%
“…However, as described in [3] the variation for one individual operator also varies greatly. [4] Operability is the ease with which the user can operate the machine as intended. As the operators are essential to the performance of the machine, operability is important.…”
Section: On Energy Efficient Mobile Hydraulic Systemsmentioning
confidence: 99%